Effects of ambient gaseous pollutants on photosynthesis, growth, yield and grain quality of selected crops grown at different sites varying in pollution levels. Issue 9 (1st September 2016) - Adrees, Muhammad; Saleem, Farhan; Jabeen, Fariha; Rizwan, Muhammad; Ali, Shafaqat; Khalid, Sofia; Ibrahim, Muhammad; Iqbal, Nazish; Abbas, Farhat
ABSTRACT: In recent decades, ambient gaseous pollution has increased due to anthropogenic activities worldwide. The studies to evaluate the adverse effects of ambient pollutants on commonly grown food crops are still limited, especially in Asian countries like Pakistan. The present study was conducted to measure the ambient pollutants in different sites of Faisalabad and their impact on growth and yield of wheat, mung bean and peas. Plants were grown in pots and placed at three sites named as control (Wire house of Government College University, Faisalabad), low pollution (LP) (Farm Area of Ayub Agricultural Research Institute) and high pollution (HP) (GT Chowk, Faisalabad) sites. Results showed that ambient ozone (O3 ) concentration was highest at HP site followed by LP site and was below AOT40 in control site. Ambient pollutants caused foliar injury in crops and decreased plant height, leaf area, biomass and grain yield. Pollutants caused a reduction in photosynthetic pigments, stomatal conductance and net photosynthetic rate and grain protein contents in all three crops. In conclusion, the ambient O3 level was highest at HP site, this current O3 level and other pollutants decreased the growth and yield of important food crops.